Four hours with dad, but 10 minutes with mom: variations in young children's media use and limits based on parent gender and child temperament - Reich, Stephanie M.; Mayfield, Keiana T.; Krager, Aubree; Franza, Deborah; Martin, Esmeralda; Cabrera, Natasha (Frontiers in Developmental Psychology, 2024)
Research on children's media use has disproportionately focused on maternal reports of use. As such, we know little of how mothers' and fathers' reports of children's media use align, how such reports might be related to parental beliefs about the benefits of media for children, or the potential differential impact of child characteristics, such as temperament and gender. Using a sample of 210 low-to-moderate income, racially and ethnically diverse families, we asked new mothers and fathers about their child's media use and limits at 9, 18 and 24 months of age. On average, reports of co-use of media, children's use of media alone, exposure to background television, diversity of daily media use, and use of media for behavior management did not significantly differ between mothers and fathers and were moderately correlated, r(df) = 0.2 -0.7. However, comparisons within dyads found that parents did not often agree on their child's media use. Couples also tended to report different limitations on use, with fathers reporting much larger time limits. For both mothers and fathers, stronger beliefs in the benefits of media when children were infants were predictive of more reported media use at 24 months. Infant negative emotionality was predictive of the use of media for behavior management for both mothers and fathers, and for other types of media use for fathers. Parents of the same child reported media use over the first two years differently, which may indicate informant effects in media research or actual differences in young children's media use with each parent. Given the risks of media use in early childhood to displace important developmental processes, understanding young children's media use within the family system is important.b count of types of media used on average day c range of mean beliefs response: 1 = strongly disagree, 2 = disagree, 3 = agree, 4= strongly agree *p<0.05, **p<0.01, ***p<0.001